Cardiac Repair With a Novel Population of Mesenchymal Stem Cells Resident in the Human Heart. (29th July 2015) - Zhang, Yuan; Sivakumaran, Priyadharshini; Newcomb, Andrew E.; Hernandez, Damián; Harris, Nicole; Khanabdali, Ramin; Liu, Guei-Sheung; Kelly, Darren J.; Pébay, Alice; Hewitt, Alex W.; Boyle, Andrew; Harvey, Richard; et al.
Abstract: Cardiac resident stem cells (CRSCs) hold much promise to treat heart disease but this remains a controversial field. Here, we describe a novel population of CRSCs, which are positive for W8B2 antigen and were obtained from adult human atrial appendages. W8B2 + CRSCs exhibit a spindle-shaped morphology, are clonogenic and capable of self-renewal. W8B2 + CRSCs show high expression of mesenchymal but not hematopoietic nor endothelial markers. W8B2 + CRSCs expressed GATA4, HAND2, and TBX5, but not C-KIT, SCA-1, NKX2.5, PDGFRα, ISL1, or WT1. W8B2 + CRSCs can differentiate into cardiovascular lineages and secrete a range of cytokines implicated in angiogenesis, chemotaxis, inflammation, extracellular matrix remodeling, cell growth, and survival. In vitro, conditioned medium collected from W8B2 + CRSCs displayed prosurvival, proangiogenic, and promigratory effects on endothelial cells, superior to that of other adult stem cells tested, and additionally promoted survival and proliferation of neonatal rat cardiomyocytes. Intramyocardial transplantation of human W8B2 + CRSCs into immunocompromised rats 1 week after myocardial infarction markedly improved cardiac function (∼40% improvement in ejection fraction) and reduced fibrotic scar tissue 4 weeks after infarction. Hearts treated with W8B2 + CRSCs showed less adverse remodeling of the left ventricle, a greater number of proliferating cardiomyocytes (Ki67 + cTnT + cells) in the remote region, higher myocardial vascular density, and greater infiltration of CD163 + cells (a marker for M2 macrophages) into the border zone and scar regions. In summary, W8B2 + CRSCs are distinct from currently known CRSCs found in human hearts, and as such may be an ideal cell source to repair myocardial damage after infarction. Stem Cells 2015;33:3100–3113 Abstract : W8B2 + cardiac resident stem cells (CRSCs) can be isolated from adult human atrial appendages using explant culture and enriched by fluorescence-activated cell sorting. Human W8B2 + CRSCs exhibit powerful paracrine activity in vitro and are cardioprotective when transplanted into the infarcted myocardium of immunocompromised rats.